Avatar: the last airbender - north and south, part one ebook - Various (Avatar: The Last Airbender,, 2016)
From National Ambassador for Young People’s Literature, Eisner Award winner, and #1  New York Times  bestseller Gene Yang ! When Aang leaves to aid Zuko with the Kemurikage, Katara and Sokka return to the Southern Water Tribe by themselves. Katara is shocked to find that her beloved village has become a bustling city, with none other than their father, Hakoda, in charge! A northerner named Malina seems to be behind this change, pushing the North and South to be more unified . . . but what are her true goals? * The official continuation of  Airbender  from its creators, Michael Dante DiMartino and Bryan Konietzko!